The American Marketing Association: A handrail for marketers and marketing history. (29th August 2014) - Cochoy, Franck
Abstract : Purpose: This paper explores the sociological process behind the development of the American Marketing Association. It shows how the shift from isolated endeavors to an organized movement happened in marketing, how and why marketing pioneers merged to build a professional body, and what this body provided to its community and to society at large. Design/methodology/approach: This paper studies the history of the AMA from the perspective of the sociology of science and relies on the marketing literature and other written sources. Findings: The paper shows that the AMA is both the result and the center of a coupling procedure. Isolated pioneers in the marketing field found it useful to communicate with those who were engaged in endeavors similar to their own. The meeting resulted in a dialogue, and the dialogue had necessitated the establishment of the AMA as a common reference point. The AMA provided the marketing community with a language and an institution that could help them to exist and move forward together. Originality/value: This paper provides an up to date account of the history of the American Marketing Association as well as a sociological analysis of its development.